Tissue Elasticity Imaging. Clinical Applications - Alam, S. Kaisar, editor 648430; Garra, Brian S., editor 648431; ScienceDirect (Online service) 7722 (Amsterdam : Elsevier, 2019)
Tissue Elasticity Imaging: Volume Two: Clinical Applications offers an extensive treatment of the fundamentals and applications of this groundbreaking diagnostic modality. Techniques and results are presented for the assessment of breast, prostate, heart, liver and thyroid tissues. For each application, details are provided on how to perform each technique, along with methods of interpretation, diagnostic criteria, quality assurance, challenges and case studies. This book is an essential resource for all researchers and practitioners (including scientists, radiologists, urologists, fellows and residents) interested in any elasticity imaging modality. As many diseases, including cancers, alter tissue mechanical properties, it is not always possible for conventional methods to detect changes, but with elasticity images that are produced by slow tissue deformation or low-frequency vibration, these changes can be displayed.